ANALISA YURIDIS TERHADAP KENDALA YANG DIHADAPI POLISI LALU LINTAS DALAM PELAKSANAAN ALTERNATIVE DISPUTE RESOLUTION (ADR) DALAM PENYELESAIAN KECELAKAAN LALU LINTAS DI WILAYAH KABUPATEN KUTAI KARTANEGARA - Helmi; Muhamad Japri; Sunarto (Collegium Studiosum Journal, 2021)
In the implementation of ADR (Alternative Dispute Resolution) against the settlement of accident cases in the kutai Kartanegara district certainly has obstacles that become obstacles for the Kutai Kartanegara Traffic Police to handle the accident case. Therefore, in this study will study further the obstacles faced by kutai Kartanegara Traffic Police to the implementation of ADR (Alternative Dispute Resolution) and solve accident cases. This research is an empirical juridical law study. Through a sociological juridical research approach. The research location is located in the Police Satlantas Kutai Kartanegara Regency, types and sources using primary data and secondary data, techniques obtained data obtained through primary data collection techniques by interview while secondary data collection techniques obtained from literature studies.